2020
DOI: 10.1002/maco.202011777
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of steel corrosion in MX80 bentonite at 120°C

Abstract: Corrosion experiments were performed on two metallic substrates, a ferritic–pearlitic steel (P285NH) and a ferritic one (Armco), in silicate environment during 30 days at 120°C. Corrosion products were characterized in terms of morphology (scanning electron microscope and transmission electron microscopy), composition (energydispersive X‐ray spectroscopy) and structure (µ‐Raman, selected area electron diffraction, X‐ray absorption near edge structure). Results show a nanometric inner layer made of compact and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Moreover, nanometric nodules of magnetite were detected by TEM inside the inner part of the siderite layer. [22,23] After 3 months, the same layout was observed with a bilayer composed of carbonate phases. The only difference was due to the formation of a local corrosion area at the metal/corrosion layer interface containing iron silicate phases.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, nanometric nodules of magnetite were detected by TEM inside the inner part of the siderite layer. [22,23] After 3 months, the same layout was observed with a bilayer composed of carbonate phases. The only difference was due to the formation of a local corrosion area at the metal/corrosion layer interface containing iron silicate phases.…”
Section: Introductionmentioning
confidence: 52%
“…Over time the diffusion limitation of the reactive species could be measured by the authors thanks to EIS spectroscopy and the layers became more compact after the SEM observations. Last, a study was conducted by Lotz et al [22,23] at 120°C in a Callovo-Oxfordian (COx) porewater containing carbonate in solution. After 1 month it was shown that the bilayer of siderite containing calcium was still present at such duration showing a compact morphology on both ferritic and ferrite-pearlitic metallic samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe is not present in these particles and consequently they do not correspond to corrosion products. Fe-rich phyllosilicates, which were for instance obtained on steel in bentonite at 120 °C [26], did not form in the experimental conditions considered here. The thickness of the corrosion product layer can be estimated from the Fe and S maps at about 20 µm.…”
Section: Cross-sectional Analysismentioning
confidence: 73%
“…Several scientific studies have been conducted on the corrosion of metallic structures within the context of the disposal of HLW (Guo, 2020). For the case of steel containers, several works have been published studying the effect of corrosion on their long-term behavior (Bulidon, 2021), (Ghahari, 2012), (Lotz, 2021), (Zhang, 2019). The corrosion process of a P285NH overpack in in-situ repository conditions has been studied in (Necib, 2017).…”
Section: Industrial Contextmentioning
confidence: 99%